Analisis Penggunaan Balok Rafter Honeycomb Untuk Struktur Gudang Tahan Gempa Dengan Metode LRFD - Guci, Jeply Murdiaman; Putri Yastari, Febi (Jurnal Bangunan, Konstruksi & Desain, 2024)
Earthquake-resistant structural planning is an important aspect in building construction in earthquake-prone areas. This study aims to analyze honeycomb rafter beams using the Load and Resistance Factor Design (LRFD) method on earthquake-resistant warehouse building structures. Honeycomb beams were chosen because of their ability to reduce the weight of the structure without sacrificing strength and stiffness. This study includes loading analysis, structural element design, and evaluation of structural performance against earthquake loads according to SNI 1726:2019 standards. The results of the study indicate that the HC 900x200x11x17 profile is adequate as a rafter or truss and the warehouse structure using honeycomb rafter beams is declared strong enough and safe in facing potential earthquake loads.